A new species of Eutyphoeus earthworm (Clitellata: Acanthodrilidae) from Mizoram, North-East India - Rodingpuia, Christopher; Hmar, Lalthanzara; Julka, Jatinder; Chawngthu, Zothansanga; Mathipi, Vabeiryureilai; Lalfelpuii, Ruth; Kumar, Nachimuthu Senthil; Gurusubramaniun, Guruswami; Lalchhandama, Kholhring; Vanlalrovi; Chhakchhuak, Lalbiakzuala (Zootaxa, 2024)
We describe here a new species of terrestrial earthworm Eutyphoeus rihnimensis sp. nov. (family Acanthodrilidae) from specimens collected at Khawrihnim, a village in Mizoram, Northeast India. The new species is distinguished from its congener members in E. gigas group in having an outgrowth that branches into four finger-like projections from the male porophores, five pairs of supra-intestinal glands in 81–88 segments, typhlosole that begins from segment 25, ventral intestinal caeca 10 that covers segments 33-34, a bidiverticulate spermathecae with a short and stout duct, and very short lateral and median diverticula among other characters. Sequence analysis based on mitochondrial cytochrome c oxidase subunit 1 (CO1) gene further warrants its distinction from known species of Eutyphoeus.